AUGMENTED REALITY AS A LEARNING FOR PROCESSING AND MARKETING WATER HYACINTH PRODUCTS IN PERUM JASA TIRTA II WITH PRISM METHOD - Ika Putri Puspitasari; Deden Witarsyah (Jurnal Informatika Teknologi dan Sains (Jinteks), 2024)
Perum Jasa Tirta II (PJT II) has launched the "Clean Lake Gold Achieved" program, aimed at utilizing water hyacinth in the Jatiluhur waters to create economically valuable handicrafts and organic fertilizers. In an effort to support its fostered MSMEs (Micro, Small, and Medium Enterprises), PJT II intends to use Augmented Reality (AR) technology as a learning and marketing tool to facilitate the study and marketing of water hyacinth products by PJT II's MSMEs. The method used is a Systematic Literature Review guided by Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), which includes identification, screening, inclusion, and eligibility of literature. The results of the PRISMA method identified 7 (seven) articles that meet criteria such as the year of publication in the last 5 years, related to AR, MSMEs, Learning, Innovation which are used as references for this study, which show that the application of AR in PJT II-assisted MSMEs can improve efficiency and product quality, as well as offer greater innovation and appeal to the market. The implementation of AR has proven effective in enhancing consumer engagement and supporting local economic growth.